E USE OF MEANS AND ELEMENTS OF VARIOUS AEROBICS IN THE DEVELOPMENT OF MOTOR ACTIVITY IN FEMALE STUDENTS AT NON-PHYSICAL EDUCATION UNIVERSITIES - БУРНЕС Анатольевна , Любовь («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
is article explores current issues in improving the teaching and training methods of female students attending academic physical education classes to enhance their motor fitness. The importance and effec- tiveness of using specially selected elements of various types of aerobics aimed at increasing the level of motor activity in female students is substantiated.